The dynamics of thickness swelling and bond strength loss of different wood-based panels at exposure to humid climate and immersion into water - Medved, Sergej (Les (Ljubljana), 2019)
An important aspect of wood-based panel usability, especially for construction, load bearing purposes or when in use for longer time, is its resistance against water. The resistance against water is related to type of wood- based panel, morphological characteristics of the constituents that panel is made of, and from the resin that was used for bonding. In an experiment we used four different wood-based panels, namely MDF (urea-formaldehyde adhesive), particleboard (urea-formaldehyde adhesive), OSB (melamine-urea-formaldehyde adhesive) and beech plywood (me- lamine-urea-formaldehyde adhesive). All panels were immersed into water and exposed to a humid climate for 90 days. Thickness swelling, compression shear strength and shear strength were determined after 1, 5, 30 and 90 days. The results showed that the highest strength decrease was observed at immersion into water. The lowest compression shear strength after immersion into water and exposure to a humid climate was determined for MDF. The occurrence of constituent failure due to mexposure to water was demonstrated through SEM analysis.
Keywords: compression shear strength; furnirna plošča; humid condition; iverna plošča; MDF; OSB; particleboard; plywood; shear strength; strižna trdnost; tlačni strig; vlažna klima; voda; water